ANALISIS KEBERGUNAAN WEBSITE SMAN 1 PRINGGARATA MENGGUNAKAN METODE HEURISTIC EVALUATION - Nitami, Dian; Ashari, Maulana; Zaen, Mohammad Taufan Asri (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
This research aims to exploit the usefulness of school websites using heuristic methods and evaluation. Likert scales are used in questionnaires to collect user perceptions of various aspects of websites, heuristic evaluations are carried out by experts to identify design problems based on usability principles. This website functions as a platform to publish information, activities and student achievements, so its quality is very important to ensure easy access and interaction for visitors. The Heuristic Evaluation method, developed by Nielsen and Molich, is used to assess the conformity of website designs with ten heuristic principles of usability, including visibility of system status, compatibility between the system and the real world, user control and freedom, standards and consistency, error prevention, better understanding rather than remembering, flexibility and efficiency, minimalist and aesthetic design, help to recognize and correct errors, and assistance and documentation.The evaluation result showthat the websiteis quite effective in meeting user needs, but there is still room for improving website speed, strenghening design consistency, and providing better efficiency, option. It is hoped that this researcher can provide guidance fordevelopers and schools to improve the quality of website, so that they can more optimally support theinformation and interaction needs of users.